Geografía histórica e impacto ambiental del programa colonizador del Carare, Santander, Colombia 1953-1957 (2015)
The purpose or this paper is to show to the academic community the innovative model for measuring environmental impact parting from a colonization program, which was constructed to answer this research question: Did the colonization agricultural program of the government period 1953-1957 contribute to extend the agricultural frontier of Carare – Santander in Colombia, in a way different from other contemporary manners or agricultural colonization? This model was constructed based on official maps of the Agustín Codazzi Geographical Institute (IGAC), new maps were developed which evidenced changes of scenery regarding: water resource, bridle paths, constructed and under construction roads, geographical boundaries and populated places. Identically, aerial photographs taken before, during and after colonization, allowed to construct new maps and to see transformations in forest, paddock, water and urban areas in order to determine modifications, which negatively impacted the environment of this region.